PERANCANGAN KATALOG PENANGKARAN KUPU-KUPU KECAMATAN HARAU KABUPATEN 50 KOTA - ALFI ALKAF SYAFIR, Drs. Nasrul Kamal, M.Sn., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Butterfly captivity garden in districts Harau is one of butterflygardens in West Sumatra. This captivity was founded and has been managed by Bujang Ranuli since 1997. The climate of Harau valley, which is cool, makes it has well-grown and varies butterfly. The increase number of forest logging and butterfly preservation to be made for souvenirs by people around endanger the butterfly that lives in this area. This absolutely makes some kinds of butterfly threatened and has not been documented yet. Lack of knowledge about butterfly makes souvenir manufacturers non-selectively chose butterfly by itskind to be processed as souvenir. Meanwhile, government’s attention and involvement in managing educational tour of butterfly are deficient still.The aim of this final work is to produce a catalog design whichdocumenting the kinds of butterfly live in Harau valley, knowledge about butterfly, butterfly conservation, and information about butterfly captivity garden in Harau valley. Thus, the design methodology used by the writer is started from collecting data method, which is through an observation, interviewing, and documenting study. Then, it is continued by data analysis method by using SWOT and creative approach. In this design, the writer will display the layout, cover, typography, and interesting colors with minimalist and naturalist image so that it is comfortable to read.The result is a media design that documenting the kinds ofbutterfly live in Harau valley, knowledge about butterfly, butterflyconservation, and information about butterfly captivity garden inHarau valley simply to be understandable by the audiences so that the message is well delivered.Keywords: butterfly, catalog, harau valley